2021
DOI: 10.1007/s11356-021-16598-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the salinity of groundwater in the HAHA syncline by the Kohonen self-organized classification (Essaouira, Morocco)

Abstract: The coastal aquifer of the Essaouira syncline (Morocco) was studied to identify the main processes at the origin of the salinization of groundwater. In fact, a multicriteria analysis approach on hydrochemical data and physicochemical parameters of the Plio-Quaternary aquifer was used to understand their spatiotemporal variation and their origins. Currently, integrated water resources management has become paramount to both local, regional, national and international. This management is favored by extreme hydro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The Principal component analysis (ACP) method was used to understand and visualize the spatial and temporal distribution of the samples. In addition, this paragraph is the result of the work of Ouzerbane (Ouzerbane et al, 2021b). Results And Discussion…”
Section: Analyse En Composantes Principales Acpmentioning
confidence: 95%
“…The Principal component analysis (ACP) method was used to understand and visualize the spatial and temporal distribution of the samples. In addition, this paragraph is the result of the work of Ouzerbane (Ouzerbane et al, 2021b). Results And Discussion…”
Section: Analyse En Composantes Principales Acpmentioning
confidence: 95%
“…Li et al (2018) applied the SOM approach on water sample dataset and found that it provided more detailed information about the dominant parameter and better classification than PCA. With the recent advancement of artificial neural network technology (ANN), SOM has sparked much attention in solving water quality related problems such as water quality assessment, effect on the landscape on groundwater, groundwater flow, salinity of water and many other studies (Belkhiri et al, 2018; Ouzerbane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such situations will recur in the future and perhaps even more frequently if they are linked to the phenomenon of deserti cation which affects West Africa and to the extent of climate change on a planetary scale. This water crisis is aggravated by the dynamic interaction of several processes that act at the local, national and global level (Bahir et al, 2002, Ouzerbane et al, 2021b. Globally, the total volume of groundwater resources is di cult to measure, but one estimate puts it at around 10.5 million km³ (Shiklomanov and Rodda, 2003), with groundwater resources remaining the main source of water fresh water on Earth, with more than 90% of fresh water immediately available (PNUE, 2008;Boswinkel, 2000).…”
Section: Introductionmentioning
confidence: 99%